Active Learning Learning Models and Smart Bottle Cap Media Can Improve Understanding of Mathematical Sums - Setyowati, Purwaningsih Heni (Universitas Sebelas Maret, 2022)
Mathematics learning is an important component in improving students' understanding and abilities in this field. However, students often have difficulty understanding abstract and complex mathematical concepts. Therefore, an effective and innovative learning model is needed to ensure students can understand and master the material well. This type of research is Classroom Action Research (PTK). The subjects of this research were class I students at SD Negeri 1 Kalitengah, Klaten City. The value collection time is carried out in 2 cycles. Data collection techniques that have been carried out use observation techniques, field notes and documentation. From the start of the Pretest, Cycle 1 and Cycle 2, grade 1 students at Kalitengah State Elementary School succeeded in fulfilling the specified KKM. The Active Learning learning model using smart bottle caps has been proven to improve students' understanding of mathematical addition. Students involved in this learning show significant improvements in their ability to add numbers, identify addition patterns, and solve math problems involving addition.